FORMATION OF CREATIVE QUALITIES OF FUTURE TEACHERS IN THE PROCESS OF PROFESSIONAL TRAINING (Pedagogy of Higher and Secondary Education, 2009)
This article deals with the question of formation of students' creative abilities. The author shows the specific conditions of students' creative abilities forming during professional training.
Keywords: creativity; creative abilities; conditions of forming of creative abilities